2022
DOI: 10.3389/fpubh.2022.929896
|View full text |Cite
|
Sign up to set email alerts
|

The effect of basic medical insurance on the changes of primary care seeking behavior: An application of hierarchical age-period-cohort analysis

Abstract: In order to encourage residents to go to primary care facilities, China has set up differentiated basic medical insurance reimbursement ratios. The study aims to use the dynamic point of view of longitudinal data to examine the changes in the impact of basic medical insurance on primary care. The data for this study comes from the Chinese Family Panel Study (CFPS) in 2010, 2012, 2014, 2016, and 2018. We adopted Hierarchal Age-period-cohort-Cross-Classified Random Effects Models (HAPC-CCREM) to examine the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Thus, primary care physicians are fully capable of performing the diagnosis, treatment, and follow-up management of this disease. In order to encourage residents to seek medical services at primary care facilities, China has formulated a tiered diagnosis and treatment policy as well as differentiated health insurance reimbursement rates [40,41]. However, to a certain extent, the results of the present study demonstrate that the implementation of the two policies is not very effective.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, primary care physicians are fully capable of performing the diagnosis, treatment, and follow-up management of this disease. In order to encourage residents to seek medical services at primary care facilities, China has formulated a tiered diagnosis and treatment policy as well as differentiated health insurance reimbursement rates [40,41]. However, to a certain extent, the results of the present study demonstrate that the implementation of the two policies is not very effective.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, access to primary care has improved following initiation of the State Council’s extensive healthcare reforms, leading to the attainment of UHC for healthcare at all levels ( 24 ). The majority of case-based payments to GPs and hospital specialists are covered by national medical insurance ( 25 ). However, our study identified several barriers, including lengthy wait lists, low acceptance of GP referrals for public programs, financial constraints associated with private programs, and limited accessibility of local programs.…”
Section: Discussionmentioning
confidence: 99%
“…In China, medical insurance reimbursement is one of the most important tools to guide patients to rational medical care, and the behavior of patients' medical needs is regulated and promoted by differentiated medical insurance reimbursement policy. One study showed that the higher the reimbursement rate of a medical institution, the greater its ability to attract residents to medical care [ 33 ]. Medical service fees should be designed in combination with measures such as family doctor system, chronic disease management, differentiated reimbursement of medical insurance, long prescriptions for essential medicines, and docking with drug catalogs in secondary and tertiary hospitals in order to coordinate the flow direction of patients with chronic diseases from tertiary hospitals to primary hospitals to further promote the effectiveness of hierarchical diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%